APPLICATION OF REMOTE SENSING TECHNOLOGIES TO DETERMINE THE CONTENT OF SOIL FERTILITY MAIN ELEMENTS - Roman STUPEN; Zoriana RYZHOK; Nazar STUPEN; Oksana STUPEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
One has applied the method of remote sensing of the Earth to calculate the introduction of the optimal rate of basic elements of nitrogen, phosphorus and potassium in assessing the state of crops in the geoinformation platform OneSoil using the selection of productive areas of land use with dense, medium and sparse vegetation based on space image data. Rates of nitrogen, phosphorus and potassium application for land use, with an area of 44.4 ha, located outside the settlement of Tyniv, Drohobych district, Lviv region on sod-gley sandy soils according to the planned yielding capacity and optimal terms of growing crops in crop rotation.